PENGARUH STRATEGI PEMBELAJARAN BERMEDIA VIDEO TUTORIAL DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR KETERAMPILAN EDITING VIDEO - Hari Setiawan; Iffah Budiningsih (Akademika, 2015)
The study was based on the problems experienced by teachers in learning videoediting skills in vocational competence broadcasting techniques. Issues under study range inquestion: "How do teachers attempt to improve video editing Learning Outcomes ThroughMedia Student Learning and Creativity? '. This study aims to: (1) Finding Step - step effectiveuse of Instructional Media and Creativity learn to develop kretivitas learners in vocationallearning video editing. (2) Obtain an overview of mastery of the material / concepts bystudents after participating in the learning process of video editing using instructional mediaand creative learning. (3) To know the perception and impression of the students on learningoutcomes (4) Getting an overview of effective use of instructional media and learning creativelearning video editing to improve learning outcomes. This research approach is quantitatifresearch method is experimental research. Procedure refers to the collection of researchempirical data including planning, implementation, evaluation.The results are as follows: (1) The application of instructional media and creativelearning can improve learning outcomes of students video editing, (2) impact on increasingstudent learning outcomes (3) Students have a positive perception of having learned thebenefits of using instructional media and creativity learning. (4) Teachers have the ability tounderstand the medium of learning and creativity and improve learning outcomes in learningvideo editing. Conclusion The results of the study are as follows: Model of Learning andCreativity learning can improve student learning outcomes. Hence, the implementation modelof learning and creativity learned in social studies learning, is effective for improving thequality of processes and learning outcomes of students from elementary schools.Finally, the study recommends to teachers in vocational Skills CompetencyBroadcasting Techniques, learning to use the media and creative learning fun, andchallenging students to be creative, practice problem solving, collaboration, fosteringcuriosity, and motivate them for more active learning. Teachers are challenged to facilitate,guide, assist, and motivate students to learn.